Use of an anti-human leukocyte interferon monoclonal antibody for the purification and radioimmunoassay of human alpha interferon. - Meurs, E (1982)
Mouse monoclonal antibody directed against human leukocyte alpha interferon (IFN-alpha) was coupled to Sepharose and used as an immunoadsorbent to purify human IFN-alpha. Leukocyte and lymphoblastoid (Namalva) IFNs were retained by the immunoadsorbent with a specificity of 80 to 100% and 40 to 60%, respectively. Human IFN-beta or -gamma and mouse IFN were not retained. The purified IFN-alpha retained its antiviral and anticellular properties as well as its ability to induce the 2-5A synthetase in human cells with a specific activity similar to that of the crude IFN. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of radioactively labeled IFN showed that it consisted of several proteins in the molecular weight range of 17,000 to 27,000. 125I-labeled IFN-alpha with a high specific activity (2,000 Ci/mmol) was used in a radioimmunoassay for the titration of IFN-alpha.